Value Engineering in Building Information Modelling for Cost Optimization of Renovation Works: a Case Study - Usman, Fathoni; Jalaluddin, Nur Adibah; Hamim, Sumi Amariena (International Journal of Engineering and Technology, 2018)
Implementation of Value Engineering (VE) in the construction industry has become a proven technique for cost optimization. This paper presents a review of the implementation of BIM in construction industry. The factors that triggered and hinder the implementation of VE and BIM in the current industry and a case study of the application of VE using BIM for cost optimization of renovation works are also discussed. The project which was used for the case study is the renovation of shop lot units to be used as a student centre where student activities will be placed. 3D models of the project were developed as BIM model that provide strong visualization when creating alternatives for VE processes. The function analysis, risk analysis and life-cycle cost analysis were applied to determine the value index for each developed alternative. It shows that the implementation had successfully reduced the cost by approximately 27% and the value of the project increased after the process.